Genetic Variability of 27 Traits in a Core Collection of Flax (Linum usitatissimum L.) - You, Frank M.; Jia, Gaofeng; Xiao, Jin; Duguid, Scott D.; Rashid, Khalid Y.; Booker, Helen M.; Cloutier, Sylvie (Frontiers in Plant Science, 2017)
Assessment of genetic variability of plant core germplasm is needed for efficient germplasm utilization in breeding improvement. A total of 391 accessions of a flax core collection, which preserves the variation present in the world collection of 3,378 accessions maintained by Plant Gene Resources of Canada (PGRC) and represents a broad range of geographical origins, different improvement statuses and two morphotypes, was evaluated in field trials in up to eight year-location environments for ten agronomic, eight seed quality, six fibre and three disease resistance traits. The large phenotypic variation in this subset was explained by morphotypes (22%), geographical origins (11%), and other variance components (67%). Both divergence and similarity between two basic morphotypes, namely oil or linseed and fibre types, were observed, whereby linseed accessions had greater thousand seed weight, seeds m-2, oil content, branching capability and resistance to powdery mildew while fibre accessions had greater straw weight, plant height, protein content and resistance to pasmo and fusarium wilt diseases, but they had similar performance in many traits and some of them shared common characteristics of fibre and linseed types. Weak geographical patterns within either fibre or linseed accessions were confirmed, but specific trait performance was identified in East Asia for fibre type, and South Asia and North America for linseed type. Relatively high broad-sense heritability was obtained for seed quality traits, followed by agronomic traits and resistance to powdery mildew and fusarium wilt. Diverse phenotypic and genetic variability in the flax core collection provides useful resource for breeding.